Man-made flood disaster in the Savanna town of Gombe / NE Nigeria. The natural hazard of gully erosion caused by urbanization dynamics and their peri-urban footprints - Balzerek, Heiko; Fricke, Werner; Heinrich, Jürgen; Moldenhauer, Klaus Martin (ERDKUNDE, 2003)
Physical and Social Geographers study hazards that affect mainly the urban poor in the fast growing town of Gombe in north-east Nigeria. Gombe, founded in 1919 grew mainly because of administrative activities from nearly 20,000 inhabitants in 1952 to 300,000 today. Caused by the peculiarities of the savanna climate, the low-level parts of the old town suffer seasonally from the menace of floods and destructive forces of gully erosion, destroying houses, bridges, urban infrastructure and even resulting in fatal casualties. By using remote sensing for change detection, the growth of the urban built-up area as well as the peri-urban foot-prints (such as the increase of farm land and firewood cutting) in the catchment area, can be documented. High resolution IKONOS satellite imagery supported the analysis of gully erosion and enabled a digital land use classification. A socio-economic survey revealed that the lack of sewage water treatment causes serious hygiene problems. Furthermore, the inadequate water supply was aggravated by the sinking water table of local wells due to channels cutting into the aquifer. The run-off in the catchment area needs to be regulated by efficient water management systems and a drainage system for sewage and surface run-off is urgently demanded.